2017
DOI: 10.1055/s-0037-1599201
|View full text |Cite
|
Sign up to set email alerts
|

Severe Form of Brachydactyly Type A1 in a Child with a c.298G > A Mutation in IHH Gene

Abstract: Brachydactyly type A1 (BDA1) is characterized by short middle phalanges. We report the case of a child with a severe form of BDA1 with complete absence of the middle phalanges of all extremities. He had c.298G > A (p.D100N) mutation in gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Reviewing published cases in addition to novel mutations identified by them, Byrnes et al [ 3 ] concluded that all BDA1 variants involving codons 95, 100, 128, 130, 131 and 154 are limited to a 59-amino acid region of the N-terminal active fragment (IHH-N) that spans codons 95–154 Soon after this review, Stattin et al [ 11 ] reported a Swedish family with a novel Arg158Cys mutation, showing that Byrnes et al’s [ 3 ] proposal is not always the case. Since then, some novel BDA1 associated variants have been reported in various populations [ 7 , 12 , 13 ]. However, to date, variants other than those involving codons 95, 100, 128, 130, 131, 154, and 158 have never been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing published cases in addition to novel mutations identified by them, Byrnes et al [ 3 ] concluded that all BDA1 variants involving codons 95, 100, 128, 130, 131 and 154 are limited to a 59-amino acid region of the N-terminal active fragment (IHH-N) that spans codons 95–154 Soon after this review, Stattin et al [ 11 ] reported a Swedish family with a novel Arg158Cys mutation, showing that Byrnes et al’s [ 3 ] proposal is not always the case. Since then, some novel BDA1 associated variants have been reported in various populations [ 7 , 12 , 13 ]. However, to date, variants other than those involving codons 95, 100, 128, 130, 131, 154, and 158 have never been identified.…”
Section: Discussionmentioning
confidence: 99%
“…This is interpreted as a common mechanism of the BDA1-causing variants [4]. Most IHH variants have been characterized as missense [1,3,[5][6][7][8][9][10][11][12], except for one insertion [13] and one deletion [14].…”
Section: Introductionmentioning
confidence: 99%
“…It impairs chondrocyte maturation and proliferation, resulting in failure of osteoblast development in endochondral bones [7]. So far, about 14 IHH pathogenic variants have been reported to be associated with BD [11][12][13][14] (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…14 IHH pathogenic variants have been reported to be association with BD [11][12][13][14][ figure 4A], and the variants are restricted to the N-terminal active fragment, and exhibit a variable outcome [4]. Variants associated with brachydactyly type A1 are known to predominantly affect codon 95, 100, 131, and 154 [3,[15][16].…”
Section: Discussionmentioning
confidence: 99%